Heterochromatin and molecular characterization of DsmarMITE transposable element in the beetle Dichotomius schiffleri (Coleoptera: Scarabaeidae) - Xavier, Crislaine; Cabral-de-Mello, Diogo Cavalcanti [UNESP]; Moura, Rita Cassia de (Springer, 2014)
Cytogenetic studies of the Neotropical beetle genus Dichotomius (Scarabaeinae, Coleoptera) have shown dynamism for centromeric constitutive heterochromatin sequences. In the present work we studied the chromosomes and isolated repetitive sequences of Dichotomius schiffleri aiming to contribute to the understanding of coleopteran genome/chromosomal organization. Dichotomius schiffleri presented a conserved karyotype and heterochromatin distribution in comparison to other species of the genus with 2n = 18, biarmed chromosomes, and pericentromeric C-positive blocks. Similarly to heterochromatin distributional patterns, the highly and moderately repetitive DNA fraction (C (0) t-1 DNA) was detected in pericentromeric areas, contrasting with the euchromatic mapping of an isolated TE (named DsmarMITE). After structural analyses, the DsmarMITE was classified as a non-autonomous element of the type miniature inverted-repeat transposable element (MITE) with terminal inverted repeats similar to Mariner elements of insects from different orders. The euchromatic distribution for DsmarMITE indicates that it does not play a part in the dynamics of constitutive heterochromatin sequences.
Keywords: Beetle; Constitutive heterochromatin; Fluorescent in situ hybridization; Transposable element; Genome; Repetitive DNA